A comparative analysis of antibacterial activity, dynamics, and effects of silver ions and silver nanoparticles against four bacterial strains. (September 2017) - Li, Wen-Ru; Sun, Ting-Li; Zhou, Shao-Lu; Ma, Yong-Kai; Shi, Qing-Shan; Xie, Xiao-Bao; Huang, Xiao-Mo
Abstract: Although both silver ions and silver nanoparticles (AgNPs) have perfect antibacterial activity, but it was assumed that AgNPs have stronger activity than that of silver ions. In this study, we make a comparative analysis of activity, dynamics, and effects of silver ions and two types of AgNPs against four bacterial strains. The minimum inhibitory concentrations (MICs) of silver ions, AgNPs (I) and AgNPs (II) were 0.5, 1 and 2 μg/mL against E. coli, 1, 2 and 8 μg/mL against P. aeruginosa, 1, 2 and 4 μg/mL against S. aureus, and 1, 2 and 2 μg/mL against S. epidermidis respectively. This experimental results showed that Ag + have stronger antibacterial activity than that of AgNPs (I) and AgNPs(II). Antibacterial dynamic curves revealed all the silver ions, AgNPs (I), and AgNPs (II) prolonged the growth lag phase of all four bacteria in a concentration-dependent manner. Furthermore, transmission electronic microscopy (TEM) observation showed that a major part of bacterial cells treated with 2 μg/mL of silver ion and AgNPs were destroyed within 5 h. The transmission electron microscopy (TEM) observation indicated that all the silver ions, AgNPs (I), and AgNPs (II) can induce severe damage in bacterial cells. The flagella of bacteria were damaged or even eliminated, which would cause movement disorders. Many holes or gaps were observed on cell surfaces, which would cause the leakage of cytoplasm and macromolecules, and leading to cell death at last. Our results suggested that silver ions have similar action mode and slightly better antibacterial activity than that of AgNPs against bacterial cells. Highlights: A comparative analysis of antibacterial activity, dynamics, and effects of silver ions and two types of AgNPs were made. Silver ions have similar action modes and slightly better antibacterial activity than that of AgNPs. Silver ions and AgNPs prolonged the growth lag phase of the bacteria in a concentration-dependent manner. Silver ions and AgNPs can induce many severe damages to bacterial cells, including the eliminated flagella.